Disease caused by non-tuberculous mycobacteria in children with cystic fibrosis. (February 2019) - Lu, Mimi; Saddi, Vishal; Britton, Philip N.; Selvadurai, Hiran; Robinson, Paul D.; Pandit, Chetan; Marais, Ben J.; Fitzgerald, Dominic A.
Abstract: Non-tuberculous mycobacterial (NTM) (especially M. abscessus complex) infections pose a considerable challenge in the management of lung disease in patients with cystic fibrosis (CF). The apparent increase in prevalence is likely multifactorial. Emergent evidence of patient-to-patient transmission and isolation of highly resistant strains is a concern for all CF centers around the world. Treatment is often long and burdensome with multiple agents. Treatment side effects are frequent and can cause significant morbidity. Although consensus guidelines provide some direction, many units are faced with the challenges of: finding drug combinations for highly resistant strains; dealing with interruptions of treatment; discussing additional facilitating procedures in the form of gastrostomy and long-term vascular access devices; as well as supporting families emotionally and psychologically through the process.